Interpreting epidemiologic distribution of total and specific IgE levels for food allergy in Southern China from 2004 to 2023: understanding the mechanisms and focusing on prevention - Mingtao Liu; Li Liu; Weitian Qi; Xianhui Zheng; Jiaxi Chen; Jiani Yao; Yufeng Li; Jinhong Lin; Xiangyu Li; Xiangyi Hu; Zhangkai J. Cheng; Huimin Huang; et al. (BMC, 2024)
Abstract Background The burgeoning prevalence of food allergy-related diseases is closely associated with geographical allergen distribution and societal lifestyle paradigms. This study aims to shed light on the distribution patterns of specific IgE (sIgE) and total IgE (tIgE) reactivity to common food allergens in the Southern Chinese populace. Methods Employing an analytical technique spanning two decades, we conducted specific IgE and total IgE on serum samples harvested from patients with food allergy-related pathologies at First Affiliated Hospital of Guangzhou Medical University from 2004 to 2023. This comprehensive examination of eight prototypical food allergens: egg white, milk, wheat, sesame, peanut, soybean, shrimp, and crab. Results Our analysis showed a 100% positivity rate for sIgE and an 86.54% positivity rate for tIgE. Milk had the highest positive response rate, followed by egg white and shrimp. Age-stratified data indicated that milk sensitization peaked in children aged 2 years or younger, while egg white sensitization peaked between 3 and 5 years of age. Sensitization rates for the remaining six allergens increased with age. Additionally, co-sensitization was observed between milk, egg white, crab, and shrimp with other allergens. Conclusion In common allergens of Southern China, egg white, milk, and shrimp ascend as the dominant subjects, underlining their imperative role in food allergy pathogenesis. This landscape-wide allergenic profiling, segregated across age clusters and enhanced by co-sensitization data, augments our power for early diagnosis and strategic intervention in food allergy diseases.